Intramuscular lipids of Mertolenga-PDO beef, Mertolenga-PDO veal and “Vitela Tradicional do Montado”-PGI veal - a. C.G. Monteiro; Fontes, M. a; Bessa, R. J. B.; Prates, J. a M.; Lemos, J. P. C. (Food Chemistry, 2012)
Three quality branded meats (n = 68), ‘‘Vitela Tradicional do Montado’’-PGI veal, Mertolenga-PDO veal and Mertolenga-PDO beef were analysed for cholesterol (HPLC-UV), a-tocopherol (HPLC-FD), fatty acid composition (GC-FID), including conjugated linoleic acid (CLA) isomeric proﬁle (Ag + -HPLC), and nutritional value of lipids. All the meats analysed had similar contents (P > 0.05) of cholesterol, a-tocopherol and intramuscular fat. In contrast, the percentage of 18:0 was lower for PGI veal, and that of 18:1 c9 was higher in PDO veal, whilst the percentage of 18:2 n6 was higher in PDO beef, relative to other two meats. The content of total CLA and the percentage of its t11,c13 isomer were higher, and the n6/ n3 ratio was lower, in PDO veal, relative to the other two meats. The data suggested that PGI veal has higher variability for most fatty acids than the other two types of meat. Finally, a discriminant analysis was conducted and the three meat types were well discriminated using the meat fatty acid proﬁle as variables.
The following values have no corresponding Zotero field: label: Beef;CLA isomers;Cholesterol;Fatty acids;Meat quality;a-Tocopherol
Keywords: a-tocopherol; Beef; Cholesterol; CLA isomers; fatty acids; meat quality

Photoprotection in evergreen Mediterranean plants during sudden periods of intense cold weather - Garcia-Plazaola, J I; OLANO, J M (Trees-Structure and …, 2003)
The photoprotective responses to an abrupt period of exceptional cold weather were studied in several Mediterranean evergreen species with different ecological requirements. The same pattern of response was observed in most of the species with little change in hydrophilic antioxidants (ascorbate and glutathione) and the carotenoid pool, an increase in the content of a -tocopherol, and a night retention of de-epoxidised xanthophylls (antheraxanthin and zeaxanthin). The accumulation of these xanthophylls correlated with a sustained decrease in maximal photochemical efficiency (Fv/Fm). This reduction in the rate of electron transport would reduce the production of superoxide in photosystem I, as well as the subsequent hydrogen peroxide and hydroxyl radical. Thereby if any transitory photooxidative stress is produced under these conditions it should be due mainly to the formation of singlet oxygen by triplet excited chlorophyll within the antenna. Since a-tocopherol is the main scavenger of singlet oxygen and lipid peroxy radicals, the large increase of this antioxidant within the species could be enough to compensate for the higher degree of photooxidative stress, playing an essential role in the survival of vegetation during the incidence of exceptional cold fronts in the Mediterranean region.
Keywords: a-tocopherol; antioxidants; photooxidative stress; xanthophyll cycle

Photoprotection in evergreen Mediterranean plants during sudden periods of intense cold weather - García-Plazaola, J. I.; Olano, J. M. (Trees-Structure and …, 2003)
The photoprotective responses to an abrupt period of exceptional cold weather were studied in several Mediterranean evergreen species with different ecological requirements. The same pattern of response was observed in most of the species with little change in hydrophilic antioxidants (ascorbate and glutathione) and the carotenoid pool, an increase in the content of a -tocopherol, and a night retention of de-epoxidised xanthophylls (antheraxanthin and zeaxanthin). The accumulation of these xanthophylls correlated with a sustained decrease in maximal photochemical efficiency (Fv/Fm). This reduction in the rate of electron transport would reduce the production of superoxide in photosystem I, as well as the subsequent hydrogen peroxide and hydroxyl radical. Thereby if any transitory photooxidative stress is produced under these conditions it should be due mainly to the formation of singlet oxygen by triplet excited chlorophyll within the antenna. Since a-tocopherol is the main scavenger of singlet oxygen and lipid peroxy radicals, the large increase of this antioxidant within the species could be enough to compensate for the higher degree of photooxidative stress, playing an essential role in the survival of vegetation during the incidence of exceptional cold fronts in the Mediterranean region.
Keywords: a-tocopherol; antioxidants; photooxidative stress; xanthophyll cycle

Susceptibility of hepatic tissue of Iberian pigs is enhanced by free-range feeding and reduced by vitamin E supplementation - López Bote, C. J.; Rey, A. I. (Nutrition Research, 2001)
The effect of feeding system (free-range vs conﬁnement) and the supplementation of concentrated feed with vitamin E and copper was investigated. Dietary copper supplementation (100 mg/kg) increased the hepatic concentration of copper in hepatic tissue (P , 0.05), reaching similar concentrations than pigs fed under free-range conditions. Free-range feeding produced higher concentration of a-tocopherol than those from pigs fed in conﬁnement with the basal level of vitamin E, but lower values than pigs fed supplemented levels, which may be attributed to the relative high concentration of a-tocopherol in the grass. Liver samples from pigs under free-range conditions showed higher susceptibility to lipid oxidation than pigs produced in conﬁnement and fed mixed diets. No signiﬁcant effect of copper was observed in hepatic tissue oxidation, but vitamin E supplementation markedly decreased oxidation
Keywords: a-tocopherol; copper; fatty acid; liver; pig